THE RELATIONSHIP OF FAMILY’S SUPPORT WITH PATIENTANXIETY LEVELS OF PREOPERATIONCATARACT (STUDIES IN THE OPTICALEYE CLINIC JOMBANG REGENCY) - Nunung Ernia; . Darsini; Marxis Udaya (Jurnal Keperawatan, 2013)
Cataract is still a dominant disease of the eye and a major cause of blindness. Cataract surgery is thetreatment measures that must be done. Patients undergoing surgery experience anxiety in order to reduceanxiety one of them needed family support, because with the support would provide psychological comfort.This research aimed to know the relation between family’s supports with Patient anxiety levels of preoperation cataract in the Optical Eye Clinic Jombang regency. This research used design of cross sectionalwith data collecting and at once time (point time approach). The population of this research was all clients ofpre cataract surgery in the Optical Eye Clinic Jombang regency in January-March a number of 14respondents with sample number of 14 respondents. The sampling technique used was sampling incidental.The independent variable was family’s support while the dependent variable was anxiety level. Dataprocessing by Editing, Coding, Scoring and Tabulating and analyzed used statistic test of spearman Rho. Theresults of this research showed of 14 respondents, half of respondents had good family’s support that’s 7respondents (50%), and half of respondents experience mild anxiety that’s 7 respondents (50%). Based onthe result of Spearman-Rho obtained result of p-value = 0,01 which means that’s less than 0,05, so ρ < αand H1 accepted. The conclusion of this research is that there’s relation between family supports withanxiety of pre-operation cataract patient in the Optical Eye Clinic Jombang regency. with the results of thisstudy can be used as input for the family that’s family’s support is very important to reduce anxiety of patientwho will perform surgery.